2016
DOI: 10.1182/blood-2016-03-703868
|View full text |Cite
|
Sign up to set email alerts
|

RNA-sequencing analysis of core binding factor AML identifies recurrent ZBTB7A mutations and defines RUNX1-CBFA2T3 fusion signature

Abstract: RUNX1 (also known as AML1 or CBFA2) and CBFB encode the a and b subunits of a heterodimeric core binding transcription factor complex involved in the development of normal hematopoiesis (reviewed by de Bruijn and Speck 1 ). Both genes are rearranged in acute myeloid leukemia (AML) with t(8;21)(q22;q22);RUNX1-RUNX1T1 and inv(16) (p13.1q22)/t(16;16)(p13.1;q22);CBFB-MYH11, which are collectively called core binding factor (CBF) AML. Targeted mutational studies have shown that both CBF AML subgroups are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 18 publications
12
50
0
Order By: Relevance
“…We also identified recurrent mutations in ZBTB7A /Pokemon (Supplemental Figure 18). The putative loss-of-function mutations identified here are consistent with recent reports of ZBTB7A acting as a tumor suppressor in RUNX1-RUNX1T1 AML 22,60 …”
supporting
confidence: 91%
“…We also identified recurrent mutations in ZBTB7A /Pokemon (Supplemental Figure 18). The putative loss-of-function mutations identified here are consistent with recent reports of ZBTB7A acting as a tumor suppressor in RUNX1-RUNX1T1 AML 22,60 …”
supporting
confidence: 91%
“…Strikingly, mutations of chromatin modifiers occurred in 42% of patients with t(8;21), yet were rare in those with inv(16). Additionally, the authors identified recurrent mutations of members of the cohesin complex in 18% of t(8;21) patients and none of the inv(16) patients, consistent with other small recent studies 6,7 (see figure panel A).…”
supporting
confidence: 87%
“…Ivey et al reported 3 cases with LRF mutations out of 223 NPM1 -mutated AML cases (1.3 %) [178]. Furthermore, LRF frameshift mutations, which generate a truncated LRF protein, were recently reported in 3 of 20 cases of AML exhibiting t(8;21) (q22;q22); RUNX1 - RUNX1T1 [179]. It remains unclear whether and how these mutations contribute to leukemogenesis.…”
Section: Zbtb Function In Hematopoietic Developmentmentioning
confidence: 99%